A Long‐Term Study of Mars Mesospheric Clouds Seen at Twilight Based on Mars Express VMC Images. Issue 7 (29th March 2021) - Hernández‐Bernal, J.; Sánchez‐Lavega, A.; del Río‐Gaztelurrutia, T.; Hueso, R.; Ravanis, E.; Cardesín‐Moinelo, A.; Wood, S.; Titov, D.
Abstract: We present the first systematic study of clouds observed during twilight on Mars. We analyze images obtained by the Visual Monitoring Camera on Mars Express between 2007 and 2020. Using an automated retrieval algorithm, we found 407 cases of clouds observed at twilight, in which the geometry of the observations allows to derive the minimum altitude, revealing that many of these clouds are in the mesosphere (above 40 km and up to 90 km). The majority of these mesospheric clouds were detected in mid‐latitudes at local autumn and winter, a new trend only hinted at by previous studies. In particular, we find a massive concentration of clouds in the southern mid‐latitudes between Terra Cimmeria and Aonia, a region where high altitude events have been previously observed. We propose that there is an unknown mechanism in these regions that enhances the probability to host high altitude clouds around the southern winter solstice. Plain Language Summary: During twilight, when the sun is below the horizon, its light can still reach clouds or mountains high above the surface, making them bright features on the dark background. This effect is sometimes seen on noctilucent clouds on Earth, and also in the mountains on the Moon. On Mars, it was first observed by ground based observers in the 1890s, and occasional observations have been later reported. We present here the first systematic study of such clouds on Mars as observed from space by the Visual Monitoring Camera (also known as the Mars webcam) onboard Mars Express. The study of clouds at twilight reveals information about their altitude, and the state of the atmosphere at this moment of the daily cycle. We analyze the occurrence of these clouds and find some new trends that previous observations had only hinted at. Key Points: We present a new methodology to detect clouds at twilight and measure their altitude. We find 407 cases, some at altitudes over 80 km High altitude clouds appear most often in mid‐latitudes during the local winter. This is a new trend when compared to previous studies High altitude clouds concentrate aerographically in a southern belt that includes Terra Cimmeria, and in clusters on northern planitias